MENINGKATKAN KEMAMPUAN LITERASI MELALUI PROGRAM RUMAH EKSPRESI DI DESA BOJONGKALONG - Fathimah, Aliya; Afifah, Fadila Nur; Pamungkas, Pras Nanda; Febiani, Reza Ari (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2023)
Literacy is one of the skills that is very important in successful learning. Apart from that, literacy also has an important role in building students' awareness of effective learning. However, unfortunately, up to now, literacy in Indonesia is still very low, as seen from United Nations Educational, Scientific and Cultural Organization (UNESCO) data, it shows that interest in reading in Indonesia is only 0.1%. This means that out of 10,000 of the nation's children, only one person likes to read. Therefore, this program aims to increase the knowledge of village communities through literacy, the community will gain information and a broad understanding of various topics and other information around them. Not only reading and writing literacy but other literacies that can be found in the midst of society's problems. Therefore, the method that will be used in this program is Participatory Action Research (PAR) where we can make changes or provide direct solutions to every problem found in the village. So it can be concluded that Rumah Expression activities are carried out to help develop children's interest in literacy in the child's own development. So in this activity, the students and children not only have skills in knowledge and insight but also have motor sensors that are more developed than children in general, which can increase their self-confidence. So that it produces achievements as expected.